2021
DOI: 10.1002/zoo.21630
|View full text |Cite
|
Sign up to set email alerts
|

The utility of social network analysis for informing zoo management: Changing network dynamics of a group of captive hamadryas baboons (Papio hamadryas) following an introduction of two young males

Abstract: Comprehensive knowledge of social groups within zoos allows for better understanding of the issues surrounding group stability and how to provide captive animals with optimal care. A developing area of sociality research that works to improve this understanding is social network analysis (SNA), which allows scientists to apply quantitative measures of group systems to represent social structure. In December 2015, Oakland Zoo introduced two new males to the hamadryas baboon (Papio hamadryas) exhibit. We examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
(78 reference statements)
2
5
0
Order By: Relevance
“…According to the association network clusters, Kusa and Milo are solitary males in relation to the rest of the group. This confirms trends reported in Radosevich et al (2021) where direct influence and centrality (a measure of the importance of a member on group structure or cohesion) of Kusa and Milo decreased as they became more peripheral members of the group, therefore an indication of early individual OMU development. Within a clan, solitary males have no access to any of the OMU's females (Pines et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…According to the association network clusters, Kusa and Milo are solitary males in relation to the rest of the group. This confirms trends reported in Radosevich et al (2021) where direct influence and centrality (a measure of the importance of a member on group structure or cohesion) of Kusa and Milo decreased as they became more peripheral members of the group, therefore an indication of early individual OMU development. Within a clan, solitary males have no access to any of the OMU's females (Pines et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…With the group density and overall clustering coefficient in both the behavioral and association networks unchanging over time, our group cohesion results show that every baboon in the group is still connected, despite the development of a second OMU. Likewise, Radosevich et al (2021) reported similar findings in this group maintaining stability measures even as measures of group cohesion decrease.…”
Section: Group Dynamicssupporting
confidence: 72%
See 2 more Smart Citations
“…Once obtained, these data have the potential to inform management strategies such as enclosure design 27 , tracking disease transmission 28 and translocation 29 all of which has the potential to impact individual and group wellbeing. Alternatively, SNA can be used to provide evidence of change following intervention 30 . Such monitoring is critical in captive populations, as the promotion of healthy social relationships are important if high-standard living conditions are to be maintained 26 , 31 .…”
Section: Introductionmentioning
confidence: 99%